Farā’id Alfāẓ al-Ḥayawānāt fī Al-Qur’ān Al-Karīm: Dirāsah fī al-I‘jāz al-Lugawi wa al-Bayāni - Elsayed Mohamed Salem Alawadi; Kamal Abdel Aziz Ibrahim; Rijal Mahdi (Maharaat: Jurnal Pendidikan Bahasa Arab, 2022)
The Qur’an has many miraculous aspects, about which there has been much talk in the past and the present. It is related to the rhetorical and linguistic aspects, and this research comes as one of these episodes that reveal the secret of the uniqueness of the words of the Holy Qur’an in general and the uniqueness of its words in particular, which came in an unprecedented manner and was organized in a non-repetitive way between the folds of its verses, so it was distinguished and unique in that it was not repeated, even its root as well. So it was consistent with the splendor of its presentation and organized in its context, in a tight linguistic system from a wise expert, and to be specific, the research was limited only to the unique words of animals and insects that were mentioned in the entire Qur’an, using the integrative approach that mixes the historical method that traces the phenomenon to the origin of its origin, and from the first to launch it and use it through the times to what it has now settled, and the linguistic analytical method, which is useful in analyzing words linguistically to understand the meaning, then the descriptive method, which monitors the characteristics of the phenomenon and its features, then clarifying this uniqueness, its rhetorical effects, and its aesthetic value. Its graphic secret is a purely artistic work that falls under the artistic method. Accordingly, the study came in three main sections and a conclusion, accompanied by the sources and references of the research. The first of them: the definition of the uniques linguistically and idiomatically, the second: the uniqueness in the critical and rhetorical heritage, and the third: the uniqueness of animals and insects in the Qur’an. Perhaps with this we add a new twist to Qur’anic studies, in fulfillment of the Qur’an, and in enriching its language.